What do we know about transgender parenting?: Findings from a systematic review. (14th April 2019) - Hafford‐Letchfield, Trish; Cocker, Christine; Rutter, Deborah; Tinarwo, Moreblessing; McCormack, Keira; Manning, Rebecca
Abstract: Transgender issues are under‐explored and marginalised within mainstream social work and social care professional practice. The experience of gender transition has a profound impact on the individuals who have diverse gender identities and their family members. We present findings from a systematic review of studies concerning the experiences of transgender parenting conducted during January–September 2017. We took a life course approach, examining the research studies that investigated the experience of people identifying as transgender, who were already parents at the time of their transition or who wished to be parents following transition. The review evaluated existing findings from empirical research on transgender parenting and grandparenting to establish how trans people negotiate their relationships with children following transition, and sought to consider the implications for professional practice with trans people in relation to how best to support them with their family caring roles. We used the Preferred Reporting Items for Systematic Review and Meta‐Analyses (PRISMA) method. Empirical studies published from 1 January 1990 to 31 April 2017 in the English language, and which had transgender parenting as a significant focus, were included in the review. Twenty‐six studies met the criteria. Key themes reported are: how trans people negotiate their relationships with children following disclosure and transition; the impact of parental transitioning on children; relationships with wider families; trans people's desires to be parents; and the role of professional practice to support trans families. We discuss how the material from the review can inform social work education and practice, including to help identify future research, education and practice priorities in this area.